A method for electrochemical oxidation conversion of a hmf crude liquid into fdca

CN122707152APending Publication Date: 2026-09-08ZHONGKE GUOSHENG (HANGZHOU) TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611043499.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-14
Publication Date
2026-09-08

AI Technical Summary

Technical Problem

这些黑腐物质会强烈吸附在催化剂活性位点上,导致催化剂迅速失活,致使FDCA的收率大幅下降(实验证明,使用商业催化剂处理粗液时收率不足20%,远低于晶体原料的90%以上)

Benefits of technology

[0020] 1) Avoiding the influence of impurities: By adopting an electrochemical oxidation method, the problem of deactivation of traditional thermocatalytic catalysts caused by impurities such as black humins in the HMF reaction crude liquid was successfully solved, and the crude liquid was directly utilized;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122707152A_ABST
    Figure CN122707152A_ABST
Patent Text Reader

Abstract

This invention discloses a method for the electrochemical oxidation of crude HMF to FDCA. The method includes: filtering the HMF-containing reaction solution to remove slag and obtain a crude solution; using humins from the filter residue as a carbon source, mixing and calcining it with a metal salt and thiourea to prepare a nitrogen-oxygen-sulfur co-doped carbon-supported nickel-cobalt sulfide catalyst; using this catalyst-modified nickel foam as the anode, electrolyzing in a strongly alkaline electrolyte with pH ≥ 13 using a three-electrode system or an anion exchange membrane device with constant current / constant voltage, oxidizing HMF at the anode to generate FDCA. This invention achieves highly efficient conversion of HMF in the crude solution, with an HMF conversion rate exceeding 98%, an FDCA molar yield of approximately 79.89%, and a maximum mass yield of 99%; in continuous membrane electrolysis, the FDCA mass yield is approximately 80%, and the purity is approximately 98%. This method eliminates the HMF crystal purification step, reduces production costs, and has significant industrial application value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of electrochemical technology, specifically relating to a method for the electrochemical oxidation of crude HMF into FDCA. Background Technology

[0002] Bio-based new materials have become a hot research area. Among them, 2,5-furandicarboxylic acid (FDCA), as a monomer of furan compounds, has unique advantages in the downstream production of bio-based polyesters (polyethylene furandicarboxylate (PEF) and its derivative polymers). Compared with the traditional PET polyester process, it significantly reduces carbon emissions and has excellent barrier properties, which has attracted the attention of academia and industry.

[0003] Currently, the mainstream industrial process for preparing FDCA typically uses 5-hydroxymethylfurfural (HMF) as a raw material, employing homogeneous or heterogeneous thermocatalytic oxidation systems. In recent years, with the reduction in renewable energy generation costs, electrocatalytic HMF oxidation (HMFOR) has demonstrated significant environmental benefits and economic feasibility due to its mild reaction conditions, use of water as a green oxygen source, and ability to couple with the hydrogen evolution reaction (HER) to achieve zero carbon emissions. Furthermore, it has made significant progress in the high selectivity and high-yield conversion of HMF crystalline raw materials.

[0004] However, the aforementioned technical route faces a severe cost bottleneck when scaled up for industrial application. In actual industrial production, the upstream process, through sugar dehydration, often produces a crude HMF reaction solution containing a large number of byproducts, rather than pure HMF crystals. To obtain a suitable feedstock for the thermocatalytic system, the crude HMF solution must undergo complex purification steps and crystallization. This purification process is not only cumbersome but also significantly increases production costs, severely hindering the economic development of downstream FDCA supply chains (such as PEF). Therefore, if the complex purification process could be bypassed, and the crude HMF reaction solution prepared upstream could be directly used for FDCA synthesis after simple treatment, it would be an ideal path with significant industrial application value.

[0005] Existing technologies struggle to achieve direct and efficient conversion of crude HMF reaction liquor, primarily due to the following insurmountable technical obstacles:

[0006] 1) Thermocatalytic systems are susceptible to impurity inhibition: In traditional homogeneous / heterogeneous thermocatalytic systems, a large amount of high molecular weight polymer impurities (commonly known as "humins") inevitably remain in the crude HMF reaction solution. These humins strongly adsorb onto the active sites of the catalyst, causing rapid catalyst deactivation and resulting in a significant decrease in the yield of FDCA (experiments have shown that the yield is less than 20% when using commercial catalysts to treat the crude solution, far lower than the more than 90% of the yield of crystalline raw materials).

[0007] 2) Research Gaps and Limitations in Electrocatalytic Systems: Existing research on HMF electrooxidation is mostly limited to high-purity HMF or low-concentration HMF crystal solutions under strongly alkaline conditions. On the one hand, strongly alkaline environments easily lead to accelerated degradation of HMF and impurities in unpurified crude solutions; on the other hand, there are currently no effective solutions to address the behavior and impact of industrial-grade HMF crude solutions, especially the complex black rot impurities, on the electrochemical reactions. Furthermore, when attempting direct electrolysis of crude solutions under weakly alkaline conditions, the slow oxidation kinetics and impurity interference often lead to rapid electrode overload, preventing normal electrolysis.

[0008] In summary, although the electrocatalytic synthesis of FDCA shows great promise, there is a lack of existing technologies that can withstand the interference of impurities such as black rot in the crude HMF reaction solution and can operate stably at industrial-grade concentrations, thereby enabling the direct and efficient preparation of FDCA from the crude solution. Summary of the Invention

[0009] To address the above problems, the present invention aims to provide a method for the electrochemical oxidation of crude HMF into FDCA.

[0010] The specific technical solution is as follows:

[0011] A method for the electrochemical oxidation of crude HMF to FDCA includes the following steps:

[0012] 1) Preparation of HMF crude reaction solution: The HMF-containing reaction solution (taken from the upstream production line) is separated by solvent, diluted and filtered to obtain HMF crude reaction solution. The filter residue is solid humins.

[0013] 2) Preparation of electrocatalyst: The solid humins obtained in step 1) are washed, dried, and pulverized, then mixed with a hydrated metal salt, thiourea, and an aqueous ethanol solution. The mixture is placed in a tube furnace and calcined under a nitrogen atmosphere. After cooling, a nitrogen-oxygen-sulfur co-doped carbon-supported nickel-based sulfide catalyst is obtained, denoted as Ni. x Co y S / NSOC;

[0014] 3) Electrochemical oxidation: using Ni x Co y S / NSOC is loaded onto nickel foam as the working electrode, forming a three-electrode system or an anion exchange membrane electrolysis device with the counter electrode and reference electrode. A strongly alkaline electrolyte with pH ≥ 13 is used as the base liquid, and the crude HMF reaction solution obtained in step 1) is added. Electrolysis is performed under constant current or constant voltage. HMF is oxidized to generate FDCA. After the reaction is completed, the product is acidified and filtered to obtain the FDCA product.

[0015] Further, in step 2), the hydrated metal salt is selected from one or more of nickel chloride hexahydrate, cobalt chloride hexahydrate, manganese chloride tetrahydrate, and copper chloride dihydrate, the mass concentration of the ethanol aqueous solution is 20%, and the mass ratio of the hydrated metal salt, the ethanol aqueous solution, thiourea, and the pulverized solid humins is 1:2:2-4:2-5.

[0016] Further, the hydrated metal salt in step 2) is a mixture of nickel chloride hexahydrate and cobalt chloride hexahydrate, with a nickel-cobalt molar ratio of 1-3:1.

[0017] Furthermore, the specific process of calcination under nitrogen atmosphere in step 2) is as follows: first, pre-calcining at 350-400℃ for 2-4 hours by raising the temperature at 10℃ / min, and then holding at 600-700℃ for 4 hours by raising the temperature at 2-5℃ / min.

[0018] Furthermore, in step 3), Ni x Co y The method for loading S / NSOC onto nickel foam is as follows: Ni x Co y S / NSOC was dispersed in a mixture of water and ethanol, Nafion solution was added, and the mixture was sonicated to obtain a dispersion. The dispersion was then dropped onto nickel foam. Ni x Co y The loading rate of S / NSOC on nickel foam was 0.3 mg / cm³. 2 .

[0019] The beneficial effects of this invention are as follows:

[0020] 1) Avoiding the influence of impurities: By adopting an electrochemical oxidation method, the problem of deactivation of traditional thermocatalytic catalysts caused by impurities such as black humins in the HMF reaction crude liquid was successfully solved, and the crude liquid was directly utilized;

[0021] 2) Achieving high-efficiency conversion: A nitrogen-oxygen-sulfur co-doped metal sulfide catalyst was designed and prepared, which can effectively catalyze the oxidation of crude HMF under strong alkaline conditions. The HMF conversion rate can reach nearly 100%, the FDCA molar yield can reach up to 79.89%, and the mass yield can reach 99%.

[0022] 3) Ensuring product quality: In the continuous membrane electrode electrolysis device, continuous feeding reaction can be carried out at a high concentration (100mM), and the final FDCA product has a purity of up to 98% and a mass yield of about 80%.

[0023] 4) Promising for industrialization: Continuous electrolytic production is achieved through an anion exchange membrane electrolysis device. The lightening of the reaction solution color confirms that impurities are converted simultaneously with HMF. The process is stable and suitable for large-scale application. Attached Figure Description

[0024] Figure 1 The LSV curves are obtained under weakly alkaline conditions using self-corroding Cu(OH)2 as the working electrode.

[0025] Figure 2 Electrochemical spectra obtained by 0.1A constant current electrolysis under weakly alkaline conditions;

[0026] Figure 3 The LSV curve is shown under strongly alkaline conditions with nickel foam as the working electrode.

[0027] Figure 4 Comparison of LSV curves of crude HMF solution and HMF crystals under the same conditions;

[0028] Figure 5 LSV curves of bare nickel foam as the working electrode under strongly alkaline conditions;

[0029] Figure 6 Electrochemical spectra obtained by 0.1A constant current electrolysis under strongly alkaline conditions;

[0030] Figure 7 These are the liquid phase detection spectra of the electrolyte before and after electrolysis;

[0031] Figure 8 A comparison of the crude solution before and after electrolysis of HMF reaction;

[0032] Figure 9 This is a schematic diagram of a membrane electrolysis device;

[0033] Figure 10 This is a graph showing the change in current density over time during membrane electrolysis. Detailed Implementation

[0034] The present invention will be further described below with reference to the accompanying drawings and embodiments, but the scope of protection of the present invention is not limited thereto.

[0035] Example 1

[0036] Comparative experiment of HMF crude reaction solution in conventional thermocatalytic oxidation system

[0037] 1) Take the reaction liquid from the production line, and after solvent separation (using a rotary evaporator), dilution and filtration, obtain a crude HMF reaction solution with a concentration of about 5 wt% (wine red or dark blackish red). The obtained solid filter residue is solid humins. Take another HMF crystal and prepare a solution with the same concentration as the crude HMF reaction solution using deionized water as a control group.

[0038] 2) Take 12g of the crude HMF reaction solution and 12g of the HMF crystal control solution from step 1) and place them into separate reaction vessels. Add 15g of sodium hypochlorite solution and 25g of sodium hydroxide solution to each reaction vessel, and then add 0.8g of commercial catalyst to each. One group contains alpha-type manganese dioxide, and the other group contains phosphotungstic acid hydrate (H3O2). 40 PW 12. xH2O), and set up a blank control group without catalyst.

[0039] 3) Seal the reaction vessel and react at a constant temperature of 50℃ for 40 min. After the reaction is completed, take a small amount of the reaction solution for HPLC analysis and determine the mass yield of FDCA. The experimental results are shown in Table 1.

[0040] Table 1. Catalytic effects of different commercial catalysts on HMF crude solution and HMF crystals.

[0041] As can be seen from Table 1, in conventional thermocatalytic oxidation systems, both alpha-type manganese dioxide and phosphotungstic acid catalysts can achieve high FDCA yields in HMF crystal solutions. However, the FDCA yield drops sharply in the crude HMF reaction solution, indicating significant catalyst deactivation. This fully demonstrates that humins impurities in the crude solution severely inhibit the activity of traditional thermocatalysts.

[0042] Example 2

[0043] Electrolysis experiment of crude HMF reaction solution under weakly alkaline conditions

[0044] 1) Electrode preparation: Commercial foamed copper was immersed in a 1 mol / L strong acid solution for 12 h, then rinsed with deionized water at least 3 times and vacuum dried at 60 °C for 2 h. The pretreated foamed copper was then immersed in a mixed solution of ammonium sulfate and sodium hydroxide with a mass ratio of 1:2 and allowed to stand for 60 min. It was then rinsed with deionized water at least 3 times and vacuum dried at 60 °C for 24 h to obtain a self-corroding Cu(OH)2 supported foamed copper electrode.

[0045] 2) Electrochemical Testing: A three-electrode system was assembled using self-corroded Cu(OH)₂ / copper foam as the working electrode, a carbon rod as the counter electrode, and Hg / HgO as the reference electrode. The electrolyte was a 0.5 M Na₂CO₃ solution (pH≈12), divided into two groups: one group consisted of 30 mL of pure electrolyte (for oxygen evolution reaction (OER) testing), and the other group consisted of 23 mL of electrolyte + 7 mL of crude HMF reaction solution (for HMF oxidation reaction (HMFOR) testing, with an HMF concentration of approximately 50 mM). Linear sweep voltammetry (LSV) was performed at room temperature with a scan rate of 5 mV / s, without IR compensation.

[0046] like Figure 1 The LSV curves showed that the oxidation current density of the HMF-containing crude solution was weak under weakly alkaline conditions, indicating that the HMF oxidation kinetics were slow and that the residual humins in the crude solution still had an adverse effect on the catalyst.

[0047] Constant current electrolysis: The above three-electrode system was replaced in an H-type electrolytic cell. The cathode chamber was filled with 30 mL of 0.5 M Na₂CO₃ electrolyte, and the anode chamber was filled with 23 mL of 0.5 M Na₂CO₃ + 7 mL of HMF crude reaction solution. Electrolysis was performed in constant current mode, with the current controlled at 0.1 A. The results are as follows... Figure 2 As shown, during constant current electrolysis, the working electrode experienced overload within a short period of time, indicating that the weakly alkaline environment could not support the rapid and stable electrolysis of crude HMF solution.

[0048] Example 3

[0049] Intermittent electrolysis of crude HMF reaction solution in an H-type electrolytic cell under strongly alkaline conditions

[0050] 1) Pretreatment of solid humins: Take the solid humins collected by filtration in Example 1, wash the solid humins with deionized water to remove soluble substances, drain the water in a tray with a pore size, and then transfer the solid humins to an oven and dry at 40°C for 24 hours. After drying, use a ball mill or pulverizer to make a uniform black powder.

[0051] 2) Electrocatalyst preparation: A hydrated metal salt (nickel chloride hexahydrate: cobalt chloride hexahydrate = 2:1), thiourea, pretreated solid humins powder, and a 20% ethanol aqueous solution were mixed and dissolved uniformly at a mass ratio of 1:2:4:2. The mixture was transferred to a ceramic boat and placed in a tube furnace. Under a nitrogen atmosphere, the mixture was heated to 350℃ at a heating rate of 10℃ / min and pre-calcined for 4 hours. Then, the heating rate was controlled at 5℃ / min to reach 700℃ and held for 4 hours. After cooling, the solid powder was collected to obtain the catalyst, which was a nitrogen-oxygen-sulfur co-doped carbon-supported metal sulfide (Ni₂Co₁S / NSOC).

[0052] 3) Preparation of working electrode: 3 mg of catalyst powder was dispersed in a mixed solution of 0.98 mL water (0.245 mL) and 0.735 mL ethanol. Then, 20 µL of Nafion solution (5 wt%) was added to the catalyst mixture and ultrasonically dispersed for 30 minutes to obtain a catalyst dispersion. 100 µL of the catalyst dispersion was uniformly dropped onto a nickel foam electrode (catalyst loading: approximately 0.3 mg·cm⁻²).

[0053] 4) LSV Performance Testing: A three-electrode system was assembled using catalyst / nickel foam as the working electrode, a carbon rod as the counter electrode, and Hg / HgO as the reference electrode. The electrolyte was 1 M KOH (pH≈14), and three sets of comparisons were set up: ① 30 mL pure 1 M KOH (OER control); ② 23 mL 1 M KOH + 7 mL crude HMF reaction solution (crude solution HMFOR, HMF concentration approximately 20 mM); ③ 23 mL 1 M KOH + 7 mL HMF crystal solution (crystal HMFOR control). LSV curves were acquired at a scan rate of 5 mV / s without IR compensation. All potentials were converted to the reversible hydrogen electrode (RHE) scale: E(RHE) = E(Hg / HgO) + 0.059 × pH + 0.098 V.

[0054] like Figure 3 and Figure 4 As shown, the LSV curves indicate that under strongly alkaline conditions, the polarization curves of crude HMFOR and crystalline HMFOR are similar in shape, and the onset potential of oxidation in the crude solution is slightly earlier than that in the crystal. This suggests that the small molecule organic matter produced by the degradation of humins in the crude solution under strong alkalinity also participates in the electro-oxidation reaction, forming a synergistic effect with HMF oxidation.

[0055] like Figure 5 The figure shows the LSV curve of the crude HMF oxidation reaction (crude HMFOR) on bare nickel foam (operating conditions are the same as catalyst / nickel foam). The results show that the HMF oxidation current density without catalyst support is lower than that with catalyst support.

[0056] 5) Constant current electrolysis in an H-type electrolytic cell: The three-electrode system was transferred into an H-type electrolytic cell, with 30 mL of 1 M KOH in the cathode chamber and 23 mL of 1 M KOH + 7 mL of HMF crude reaction solution in the anode chamber. Constant current mode was used, controlling the current at 0.1 A (corresponding to a current density of approximately 0.1 A / cm²), and electrolysis was performed at room temperature (using 23 mL of 1 M KOH + 7 mL of HMF crystal solution as a control).

[0057] The results are as follows Figure 6-8 As shown, after constant current electrolysis for approximately 20,000 s, HPLC analysis revealed that the HMF conversion rate was approximately 98%, the molar yield of FDCA was approximately 79.89%, and the mass yield was approximately 99%. The anolyte color changed significantly from a deep blackish-red to a lighter shade before and after electrolysis, confirming the simultaneous oxidation and consumption of humins and related organic matter. Compared to the electrolysis of crystalline HMF, the Faraday current efficiency of the crude solution electrolysis was slightly reduced, but highly selective FDCA preparation was still achieved.

[0058] Example 4

[0059] A strongly alkaline anion exchange membrane electrolysis device continuously electrolyzes crude HMF reaction liquor.

[0060] 1) Electrolysis apparatus setup: An anion exchange membrane electrolyzer with an effective area of ​​2 cm × 2 cm (e.g., ...) is used. Figure 9 As shown), a Ni-loaded anode is installed on the anode side. x Co y The S / NSOC catalyst consists of foamed nickel (catalyst loading 0.3 mg / cm²), with bare foamed nickel packed on the cathode side, separated by an anion exchange membrane, and clamped and fixed by electrode plates at both ends. The anode feed is a 1 M KOH solution containing crude HMF (HMF concentration approximately 100 mM), and the cathode circulating solution is a pure 1 M KOH solution.

[0061] 2) Continuous electrolysis operation: A peristaltic pump is used to pump the anolyte into the anode chamber at a flow rate of 10 mL / h, and the effluent is collected separately; the catholyte is pumped into the cathode chamber at a flow rate of 200 mL / h for circulation. The constant electrolysis voltage of 1.68 V (vs. RHE) is controlled for continuous operation at room temperature.

[0062] 3) Product collection: After continuous electrolysis for 28.6 h, the anolyte was combined, acidified to acidic, filtered, and the white solid precipitate was collected, which was the crude FDCA product. The obtained solid was weighed, and its purity and structure were characterized by HPLC.

[0063] like Figure 10 As shown, the current density remained stable during continuous electrolysis without significant decay, indicating that the catalyst and electrolysis system have good stability during long-term operation.

[0064] The final HMF conversion rate was close to 100%. After acidification and filtration, approximately 3.5 g of FDCA solid was obtained, with a mass yield of approximately 80% and a purity of approximately 98% as determined by HPLC. The color of the anolyte gradually lightened from its initial dark color, further confirming that colored impurities in the crude solution (including humins degradation products) were continuously oxidized and removed during electrolysis.

Claims

1. A method for the electrochemical oxidation conversion of crude HMF into FDCA, characterized in that, Includes the following steps: 1) Preparation of crude HMF reaction solution: The HMF-containing reaction solution is separated by solvent, diluted and filtered to obtain crude HMF reaction solution. The filter residue is solid humins. 2) Preparation of electrocatalyst: The solid humins obtained in step 1) are washed, dried, and pulverized, then mixed with a hydrated metal salt, thiourea, and an aqueous ethanol solution. The mixture is placed in a tube furnace and calcined under a nitrogen atmosphere. After cooling, a nitrogen-oxygen-sulfur co-doped carbon-supported nickel-based sulfide catalyst is obtained, denoted as Ni. x Co y S / NSOC; 3) Electrochemical oxidation: using Ni x Co y S / NSOC is loaded onto nickel foam as the working electrode, forming a three-electrode system or an anion exchange membrane electrolysis device with the counter electrode and reference electrode. A strongly alkaline electrolyte with pH ≥ 13 is used as the base liquid, and the crude HMF reaction solution obtained in step 1) is added. Electrolysis is performed under constant current or constant voltage. HMF is oxidized to generate FDCA. After the reaction is completed, the product is acidified and filtered to obtain the FDCA product.

2. The method for electrochemically converting crude HMF into FDCA as described in claim 1, characterized in that, In step 2), the hydrated metal salt is selected from one or more of nickel chloride hexahydrate, cobalt chloride hexahydrate, manganese chloride tetrahydrate, and copper chloride dihydrate. The mass concentration of the ethanol aqueous solution is 20%, and the mass ratio of the hydrated metal salt, the ethanol aqueous solution, thiourea, and the pulverized solid humins is 1:2:2-4:2-5.

3. The method for electrochemically converting crude HMF into FDCA as described in claim 2, characterized in that, The hydrated metal salt in step 2) is a mixture of nickel chloride hexahydrate and cobalt chloride hexahydrate, with a nickel-cobalt molar ratio of 1-3:

1.

4. The method for electrochemically converting crude HMF into FDCA as described in claim 2, characterized in that, The specific process of calcination under nitrogen atmosphere in step 2) is as follows: first, pre-calcine at 350-400℃ for 2-4 hours by raising the temperature at 10℃ / min, and then hold at 600-700℃ for 4 hours by raising the temperature at 2-5℃ / min.